Analisis Faktor-faktor yang Berhubungan dengan Kepuasan Karyawan terhadap Kualitas Manajemen di RSUP Prof. Dr. R. D. Kandou Manado - Nadya L. Runtuwene; Erwin G. Kristanto; Gustaaf A.E. Ratag (Medical Scope Journal, 2023)
Abstract: Hospital as a service institution must consider the job satisfaction of its employees, so that the excellent service can be achieved which will improve the quality of hospital services. This study aimed to find out the factors related to employee satisfaction with the quality of management at Hospital Prof. Dr. R. D. Kandou Manado and analyze the relationship of these factors. This was a descriptive and analytical study with a cross sectional design through a survey with a quantitative approach. Samples were 350 employees at Prof. Dr. R. D. Kandou Hospital that met the inclusion and exclusion criteria. Independent variables were hospital policy, salary, work situation, career advancement or promotion, and job responsibilities meanwhile dependent variable was satisfaction. A questionnaire was used as the assessment instrument. The univariate analysis showed that most respondents were satisfied with hospital policies (83%), salary (87%), work situation (93%), career advancement (81%), hospital responsibilities (91%), and employee satisfaction (90%). The bivariate analysis showed that there was a relationship between employee satisfaction with hospital policy factors, salary, work situation, career advancement and responsibility (p=0.000). Meanwhile, the multivariate analysis showed that the most related factor to employee satisfaction with the management of hospital was work situation with a value of 39.652 (p=0.004). In conclusion, factors that influence job satisfaction include hospital policies, salary, work situation, responsibility, career advancement or promotion. The most related factor is work situation. Keywords: employee satisfaction; management quality   Abstrak: Rumah Sakit (RS) sebagai institusi pelayanan harus mempertimbangkan kepuasan karyawan agar pelayanan prima dapat tercapai yang akan meningkatkan mutu pelayanan RS. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan kepuasan karyawan terhadap kualitas manajemen di RSUP Prof. Dr. R. D. Kandou, Manado dan menganalisis hubungan faktor-faktor tersebut. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang melalui survei dengan pendekatan kuantitatif. Sampel penelitian ialah 350 karyawan di RSUP Prof Dr. R. D. Kandou Manado yang memenuhi kriteria inklusi dan eksklusi. Variabel bebas ialah kebijakan rumah sakit, gaji, situasi pekerjaan, peningkatan karir, dan tanggung jawab pekerjaan, sedangkan variabel terikat ialah kepuasan. Instrumen penilaian dengan menggunakan kusioner. Hasil analisis univariat mendapatkan bahwa sebagian besar responden merasa puas dengan kebijakan rumah sakit (83%), gaji (87%), situasi pekerjaan (93%), peningkatan karir (81%), tanggung jawab rumah sakit (91%), dan kepuasan karyawan (90%). Hasil analisis bivariat mendapatkan bahwa terdapat hubungan antara kepuasan karyawan dengan faktor kebijakan rumah sakit, gaji, situasi pekerjaan, peningkatan karir dan tanggung jawab (p=0,000). Hasil analisis multivariat mendapatkan faktor yang paling berhubungan dengan kepuasan karyawan terhadap manajemen RS ialah situasi pekerjaan dengan nilai 39,652 (p=0,004). Simpulan penelitian ini ialah faktor-faktor yang memengaruhi kepuasan karyawan ialah kebijakan rumah sakit, gaji, situasi pekerjaan, peningkatan karir dan tanggung jawab. Faktor yang paling berhubungan ialah situasi pekerjaan. Kata kunci: kepuasan karyawan; kualitas manajemen